2020
DOI: 10.1097/brs.0000000000003788
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between Facet Tropism and Intervertebral Disc Herniation in the Subaxial Cervical Spine

Abstract: Study Design. A retrospective case–control study. Objective. Investigating the correlation between the facet tropism (FT) and subaxial cervical disc herniation (CDH). Summary of Background Data. Although debatable, it was widely reported that FT was associated with lumbar disc herniation. However, the exact correlation between FT and subaxial CDH is still unclear. Methods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…There are conflicting views on the relevance of spinal tropism-in particular, whether tropism in the spine is related to degenerative changes of the facets or discs. A recent systematic review with meta-analysis [6] found that there is a relationship between tropism and degenerative changes for both the lumbar and cervical spines, and a further study in the cervical spine reinforced these findings [7]. Such changes are paradoxically thought to result from tropism either limiting movement [8] or increasing instability [9], but in either case, the result is thought to be increased stresses on the facets and discs [10].…”
Section: Introductionmentioning
confidence: 99%
“…There are conflicting views on the relevance of spinal tropism-in particular, whether tropism in the spine is related to degenerative changes of the facets or discs. A recent systematic review with meta-analysis [6] found that there is a relationship between tropism and degenerative changes for both the lumbar and cervical spines, and a further study in the cervical spine reinforced these findings [7]. Such changes are paradoxically thought to result from tropism either limiting movement [8] or increasing instability [9], but in either case, the result is thought to be increased stresses on the facets and discs [10].…”
Section: Introductionmentioning
confidence: 99%
“…The facet tropism is interpreted as the asymmetry between the left and the right angles of the facet joints, along with one joint, which has a more sagittal positioning than the other. This was intended to enhance risks for the degradative disorder in the equivalent disc herniation and the rotational variability of the spinal segment [ 7 ]. The degenerative spondylolisthesis is recognized as a lumbar vertebral body sliding ahead of the adjoining vertebral body without the neural arch flaw because of the variable effect of the progressive variation.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the side of disc herniation was associated with the side of larger axial FO, meaning that the direction of herniation preferred the side of greater FO. It has been demonstrated in a previous cervical study that the greater facet angle at the left or right side did not affect the side of herniation in patients with cervical disc herniation [25]. This could be explained by the different experimental design, study population and methodology.…”
Section: Discussionmentioning
confidence: 86%
“…A rat model study reported that participating factors to disc herniation were not only axial compression but exion and torsion [39]. It is commonly held that cervical facet joints are 3-dimentional, including that axial cervical spine is responsible for rotation movement, sagittal cervical spine is responsible for exion-extension, and coronal cervical spine is responsible for lateral bending [24,25]. Previous biomechanical ndings proposed that the biomechanical effects of FT rather than FO contributed to the increases in disc stress and facet joint contact at the corresponding segment [32,40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation